Análisis y evaluación financiera de la creación de un nuevo proyecto seguros para tarjetas de débito emitidas por el banco del pichincha patrocinada por aig metropolitana cia. de seguros y reaseguros - Taipe, Carolina (2009)
The insecurity generated by the delinquency in your multiple manifestations, has turned into a topic of high worry on the part of the Ecuadoran citizenship. During the last years the assaults have multiplied at gunpoint, kidnappings and thefts with violence as well as the dizzy development of new modalities of swindles and thefts. The thefts in cash dispensers are among the ten most frequent types of assault. In 15 days, the claimants assured to have lost 13 credit cards, 16 of debit and two passbooks of saving, without specifying the values in risk. "To be fixed well in the cashier, not to use it if it is obvious slightly strange and to warn immediately to the bank if the device swallows the card ", apparently it constitutes the golden rule that, according to the Headquarter of the Police and Financial Institutions, the users of the cash dispensers must follow to minimize the risk of being victims of one defrauds. Nevertheless, it is impossible to give more concrete recommendations, because there are thousand variants of this type of theft. Nevertheless, it is impossible to give more concrete recommendations, because there are thousand variants of this type of theft. There are devices that catch the card in the groove, cameras that record the secret number, devices that directly read the magnetic band and duplicate it without the user realizes nothing, among others. The swindlers who operate in the cash dispensers are increasingly and rely on more advanced means. This criminal activity has reached a high level of engineering development; the delinquents have evolved of form parallel to the introduction of new measures of safety. The Financial Institutions have knowledge